Interrelations of the fraktalkin level and echocardi-oskopic indicators at the arterial hypertension, sten-ocardia tension and their combination - D. S. Tarasochkina; E. A. Polunina; I. V. Sevostyanova; L. P. Voronina; B. I. Kantemirova (Кубанский научный медицинский вестник, 2015)
To reveal the interrelation between the level of the fraktalkin plasma and indicators of the dopplerechocardiography (ECHO-CS) were examined 135 patients with the arterial hypertension (AH), stenocardia tension (ST) and their combination (AH+ST). It was established the influence of the system of inflammation and giperfraktalkinemiya on the structure and a functional condition of the heart at the patients with the cardio-vascular pathology. During the isolated AH and ST there were observed interrelations of the weak force between the level of the fraktalkin and some indicators of ECHO-CS. During the combination of AH+ST there were observed the strong correlative interrelations of the level of fraktalkin with a number of the indicators of the ECHO-CS, which reflected with a condition of both the left, and the right heart sections and a condition of the pulmonary haemodynamic. So the correlative interrelation between the level of the fraktalkin and functional class of heart failure were observed.